To assess the Effectiveness of Self-Instructional Module on Knowledge regarding common worm Infestation among School Children at Rural School of Rangareddy District - Yadav, Seema Yadav; Sravanthi (International Journal of Psychosocial Rehabilitation, 2025)
OBJECTIVES OF THE STUDY: • To assess the level of knowledge regarding common worm infestation among school children by • To develop and administer self-instructional module on common worm • To determine the effectiveness of self-instructional module on knowledge regarding common worm infestation among school children by posttest. • To find out the association between level of knowledge regarding common worm infestation with selected demographic variables. The research approach adopted for the study was a pre-experimental approach. The population for present study consists of school children who can read and understand the Telugu and English. The size of the sample was 60. The sample was selected through non-probability purposive sampling technique. The Standard tool method was used to collect the required data from school children. The reliability of the questionnaire was assessed by split half method. Correlation Co-efficient was calculated by using Karl Pearson Formula and a value of r=0.9469 was obtained. The investigator conducted study at rural school, Rangareddy Dist.